CHINESE HERBAL MEDICINE: A SAFE ALTERNATIVE THERAPY FOR URINARY TRACT INFECTION IN PATIENTS WITH RENAL INSUFFICIENCY - Tong, YanQing; Leng, Yan; Bai, JingLi (African Journal of Traditional, Complementary and Alternative Medicines, 2011)
We have used reduced doses of Chinese herbs for estimation of urinary tract infections (UTIs) patients with stable impairment of renal function. A total of 33 adult female patients with moderately impaired renal function and symptomatic UTIs were included in this study. Urine cultures were carried out. Patients were monitored clinically and with various laboratory tests. Chinese herbal concoction divided by milligrams of creatinine per 100 ml were orally administrated for ten days. Three patients were excluded from final analysis. Most of the patients responded symptomatically to treatment. Chinese herbs eradicated the primary pathogen in 68.7% of the patients at the day 10 of treatment. Two patients relapsed (one had abbreviated courses of therapy) 6 to 8 days posttreatment. Organisms which recurred included Escherichia coli and Pseudomonas aeruginosa. Bacterial reinfections occurred 5 to 8 days posttreatment in four patients. Adverse reactions observed among the 30 patients were rare. Nausea (6.67%) and mild elevation of hepatic enzymes (3.33%) were probably drug related. Nausea disappeared when the therapy ended. Elevated hepatic enzymes resumed at the 2-week follow-up. Two patients demonstrated slight increases in serum creatinine on day 10 of treatment. One patient had a 12.5% elevation over baseline and the other had a 13.0% elevation. Serum creatinine values had improved in these two patients at 4-week follow-up. Chinese herbal medicine was effective and safe in the treatment of UTIs with renal insufficiency. .